More polymorphic microsatellite markers in the European sea bass (Dicentrarchus labrax L.) - Ciftci, Y. (2014)
We provide details of five microsatellite loci screened in 163 individual sea bass. Large numbers of alleles were observed at three loci (20–25) and heterozygosities ranged from 0.52 to 0.86. These loci should prove useful for population genetic studies and for the pedigree analysis and genetic management of this species in aquaculture.